Advanced engineering of third-generation lysins and formulation strategies for clinical applications. (2nd September 2020) - De Maesschalck, Vincent; Gutiérrez, Diana; Paeshuyse, Jan; Lavigne, Rob; Briers, Yves
Abstract: One of the possible solutions for the current antibiotic resistance crisis may be found in (often bacteriophage-derived) peptidoglycan hydrolases. The first clinical trials of these natural enzymes, coined here as first-generation lysins, are currently ongoing. Moving beyond natural endolysins with protein engineering established the second generation of lysins. In second-generation lysins, the focus lies on improving antibacterial and biochemical properties such as antimicrobial activity and stability, as well as expanding their activities towards Gram-negative pathogens. However, solutions to particular key challenges regarding clinical applications are only beginning to emerge in the third generation of lysins, in which protein and biochemical engineering efforts focus on improving properties relevant under clinical conditions. In addition, increasingly advanced formulation strategies are developed to increase the bioavailability, antibacterial activity, and half-life, and to reduce pro-inflammatory responses. This review focuses on third-generation and advanced formulation strategies that are developed to treat infections, ranging from topical to systemic applications. Together, these efforts may fully unlock the potential of lysin therapy and will propel it as a true antibiotic alternative or supplement.